THE INFLUENCE OF CULTURAL, SOCIAL, BRAND IMAGE, AND PERCEPTION OF QUALITY ON PURCHASING DECISION AT JINJJA CHICKEN - Efin Shu; Angellica Nathania Benida (Jurnal Ekonomi, 2023)
Jinjja Chicken is a restaurant with a main menu of Korean fried chicken. The restaurant experienced a decrease in revenue due to increasing competition from other Korean restaurants. Customers have several factors in terms of shaping consumer behavior, one of which is culture and social. The development of Korean restaurants in the city of Medan is increasingly developing. At present the development of Korean restaurants in Medan makes Jinjja Chicken has an urgency to improve its image. There are still problems at Jinjja Chicken experienced by consumers who have not received optimal service. The purpose of this study was to determine the influence of cultural, social, brand image, and perceived quality on purchasing decisions. This research was conducted using quantitative, descriptive, and causal methods. The test results have passed the validity, reliability, classic assumption tests of normality, multicollinearity, and heteroscedasticity tests. The population used is all customers of Jinjja Chicken and the total sample is 140 respondents using convenience sampling. The results of hypothesis testing show that culture, social, brand image, and perceived quality have positive and significant effect on purchasing decisions partially and simultaneously so that the hypotheses H1, H2, H3, H4 are accepted. The coefficient of determination is 55.5% and the rest is influenced by other variables not examined. Recommendations for Jinjja Chicken are adding other menus that are in accordance with Korean culture, providing special room for family events, providing promotional programs to consumers, implementing hygiene and safety standards in handling food, and implementing loyalty program for customers.